The influence of leaf litter diversity and soil fauna on initial soil erosion in subtropical forests. Issue 11 (17th March 2015) - Seitz, Steffen; Goebes, Philipp; Zumstein, Pascale; Assmann, Thorsten; Kühn, Peter; Niklaus, Pascal A.; Schuldt, Andreas; Scholten, Thomas
Abstract Although the protective role of leaf litter cover against soil erosion is known for a long time, little research has been conducted on the processes involved. Moreover, the impact of soil meso‐ and macrofauna within the litter layer on erosion control is not clear. To investigate how leaf litter cover and diversity as well as meso‐ and macrofauna influence sediment discharge in subtropical forest ecosystems, a field experiment has been carried out in Southeast China. A full‐factorial random design with 96 micro‐scale runoff plots and 7 domestic leaf species was established and erosion was triggered by a rainfall simulator. Our results demonstrate that leaf litter cover protects soil from erosion (−82 % sediment discharge on leaf covered plots) by rainfall and this protection is removed as litter decomposes. The protective effect is influenced by the presence or absence of soil meso‐ and macrofauna. Fauna presence increases soil erosion rates significantly by 58 %, while leaf species diversity shows a non‐significant negative trend. We assume that the faunal effect arises from arthropods slackening and processing the soil surface as well as fragmenting and decomposing the protecting leaf litter covers. Even though the diversity level did not show a significant influence, single leaf species in monocultures show rather different impacts on sediment discharge and thus, erosion control. In our experiment, runoff plots with leaf litter from Machilus thunbergii showed the highest sediment discharge (68.0 g m−2) whereas plots with Cyclobalanopsis glauca showed the smallest rates (7.9 g m−2). Copyright © 2015 John Wiley & Sons, Ltd.